Towards online security: Key drivers of poor user behaviour and recommendations for appropriate interventions - M. J. Butler (South African Journal of Business Management, 2014)
Online commerce has grown significantly and securing this channel of commerce is of vital importance for organisations. In the quest to secure the online world, users are often referred to as the weakest link in online security since theirbehaviour could impact negatively on systems security. User education and awareness programmes to develop and enhance the required skills and appropriate frame of mind are common approaches to improve online security.Focussing on the drivers of change in user's online security behaviour can assist in defining appropriate interventions. Key human behaviour models where used to define these drivers. The drivers of change in online security behaviour wasused to design an instrument used to survey South African online consumers to determine the prevalence, or not, of factors that determine secure or unsecure behaviour.The data from the survey was analysed to highlight the Knowledge, Capability and Motivation to behave in a secure manner, as well as te st for potential aspects that have influenced past behaviour and that could potentially influencefuture behaviour. Based on the determinants of behaviour, as well as identified deficiencies in password behaviour as identified by the survey, a list of potential considerations for the designers ofiS security interventions is presented.
Keywords: 650